Refuelling a special friendship : Canada and the Caribbean states - Campbell, Frank A. (North-South Institute OttawaCA, 1992)
Assesses the relationship between Canada and the Commonwealth Caribbean in the light of the changing global situation. Looks at things that have brought them together such as trade investment, transportation, Canadian aid, people, agencies, conferences and institutions, and formal linkages. Examines how the Caribbean rises to meet its challenges and briefly touches on the work of the West Indian Commission, trade agreements and NAFTA.